Studies on motivation and EFL teaching and learning in Ecuador - Soto, Sandy T. (2024)
The purpose of this work is to document the investigations on motivation and EFL teaching and learning in elementary school, secondary school, and university settings in Ecuador that have been published since 2010 until November 2023. The literature review technique was used to answer the three research questions formulated for this study. The questions inquired into what has been investigated, the main findings, and the research gaps of the literature concerning motivation and EFL teaching and learning in Ecuador. 19 research articles and 1 book chapter composed the unit of analysis. Overall findings reveal that studies have focused on investigating the factors that impact students’ motivation to learn EFL as well as the strategies, techniques and methods that motivate students to learn this language. Motivation on EFL teaching and learning in Ecuador has been highly explored in higher education. Yet, there is little literature on the topic in relation to primary and secondary school. Research gaps indicate the need for longitudinal studies as well as studies that focus on: motivation and cultural factors, the implementation of appropriate strategies to make the integration of supplemental resources more motivating for students, training of teachers on motivation-based teaching practices, motivation and higher-order thinking, reading and motivation, learning content adjustment to motivate learners, and motivation and language learning in virtual settings.